2007
DOI: 10.1017/s1751731107392732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among three approaches for evaluation of sexual precocity in Nellore cattle

Abstract: Restricted breeding seasons used in beef cattle produce censored data for reproduction traits measured in regard to these seasons. To analyze these data, adequate methods must be used. The objective of this paper was to compare three approaches aiming to evaluate sexual precocity in Nellore cattle. The final data set contained 6699 records of age at first conception (AFC14) (in days) and of heifer pregnancy (HP14) (binary) obtained from females exposed to the bulls for the first time at about 14 months of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
8
0
1
Order By: Relevance
“…The heritability estimate of 0.53 ± 0.03 obtained in this study for HP on the liability scale indicates the importance of genetic variance for this trait as well. Similar heritability values in Nellore cattle (0.57 ± 0.11, 0.61 ± 0.10, and 0.58 ± 0.13) were reported by Eler et al (2002Eler et al ( , 2004 and Pereira et al (2007), respectively. Pereira et al (2006), using survival analysis for Nellore cattle, estimated a value of 0.51 for heritability, on the logarithmic scale, of age at first conception for females exposed to sires for the first time at about 14 mo of age.…”
Section: Estimates Of Heritabilitiessupporting
confidence: 79%
See 2 more Smart Citations
“…The heritability estimate of 0.53 ± 0.03 obtained in this study for HP on the liability scale indicates the importance of genetic variance for this trait as well. Similar heritability values in Nellore cattle (0.57 ± 0.11, 0.61 ± 0.10, and 0.58 ± 0.13) were reported by Eler et al (2002Eler et al ( , 2004 and Pereira et al (2007), respectively. Pereira et al (2006), using survival analysis for Nellore cattle, estimated a value of 0.51 for heritability, on the logarithmic scale, of age at first conception for females exposed to sires for the first time at about 14 mo of age.…”
Section: Estimates Of Heritabilitiessupporting
confidence: 79%
“…On average, puberty in Nellore breed (Bos indicus) is expressed at a later age, and the genetic variability of HP seems to be much greater (Eler et al, 2004). Eler et al (2004) and Pereira et al (2007) suggested the use of HP as a selection criterion, with the aim of indicating early puberty in the Nellore breed.…”
Section: Estimates Of Heritabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the heritability estimate of 0.54 ± 0.03 obtained in this study for HP confirms the existence of significant genetic variance for this trait as well. Similar heritability values in Nellore cattle (0.57 ± 0.11, 0.61 ± 0.10, and 0.58 ± 0.13) were reported by Eler et al (2002Eler et al ( , 2004 and Pereira et al (2007). However, in Bos taurus populations, Evans et al (1999) and Doyle et al (2000) found lower heritability estimates for Hereford and Angus breeds (0.14 ± 0.18, and 0.21 ± 0.12, respectively).…”
Section: Heritabilitiessupporting
confidence: 69%
“…Table 2. Spearman correlation of all animals (above diagonal) and sires (below diagonal) between predicted breeding values of AFC trait and percentage of sires in common between models at 1% (above diagonal) and 10% (below diagonal) selection percentages Pereira et al (2007) studying age at first conception in Nellore cattle population. These authors reported that when considering just the sires the correlation was even lower; and lower the number of animals, more sensitive is the Spearman correlation to slight changes in classification.…”
Section: Methods Comparisonmentioning
confidence: 99%